2016
DOI: 10.3732/ajb.1500224
|View full text |Cite
|
Sign up to set email alerts
|

What can local and geographic population limits tell us about distributions?

Abstract: These cases illustrate two contrasting spatial scales, yet agree in their illustration of strong habitat limitation. We end by discussing future avenues of research and by suggesting ways botanical researchers can frame their studies to maximize information gained on species requirements, distribution limits, and conservation among varying spatial scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…Hilgard, 3230 m, by P. Raven, Record ID: CAS 389948). In a seed‐sowing experiment at field sites with habitats similar to those occupied by M. laciniatus , but beyond the current elevation limits, plants failed to establish self‐sustaining populations during 5 years of post‐experiment observation (Sexton & Dickman ), further indicating stable, contemporary range limits.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hilgard, 3230 m, by P. Raven, Record ID: CAS 389948). In a seed‐sowing experiment at field sites with habitats similar to those occupied by M. laciniatus , but beyond the current elevation limits, plants failed to establish self‐sustaining populations during 5 years of post‐experiment observation (Sexton & Dickman ), further indicating stable, contemporary range limits.…”
Section: Methodsmentioning
confidence: 95%
“…Changes in habitat quality and availability or biological interactions (e.g. competition) just beyond current limits may be important (Sexton & Dickman 2016). The change to chaparral environments at lower elevations, which lack winter snowpack, and to drier eastern Sierra environments beyond the crest at higher elevations (Barbour et al 2007) may represent critical ecological transitions where the slow-draining, rocky seeps upon which M. laciniatus grow become rare or absent.…”
Section: Regarding Causes Of Range Limitsmentioning
confidence: 99%
“…Dispersal and habitat limitation studies in Mimulus leptaleus and Mimulus laciniatus in the California Sierra Nevada found that habitat limitation was more important than dispersal ability in limiting range expansion (Sexton and Dickman, 2016). However, in some cases there may be a lack of overlap between a species' future latitudinal or elevational range and the habitat needed to support it (Bellard et al, 2012).…”
Section: Habitat Specificitymentioning
confidence: 99%
“…Predicting range shifts and population persistence in the face of climate change is a major ecological challenge, one that is further complicated by the potential for local adaptation (LA) to historical climate. Many species show strong reductions in performance when individuals are moved beyond range boundaries, suggesting that many distributional limits are driven by species’ climate tolerances (Hargreaves, Samis, & Eckert, ; Lee‐Yaw et al, ; Sexton & Dickman, ). But broad climate tolerances at the species level are generally comprised of narrower, locally adapted tolerances at the scale of populations (e.g., Angert, Sheth, & Paul, ; Hoffman, Anderson, & Hallas, ; Kelly, Sanford, & Grosberg, ; Sheth & Angert, ).…”
Section: Introductionmentioning
confidence: 99%